Sex differences in ST-segment elevation myocardial infarction patients treated by primary percutaneous intervention - Pascal Meier; Stéphane Cook; MARIO TOGNI; Diego A Arroyo; Serban Puricel; Selma T Cook; Laure Allemann; Malica Cook; Thais Pittet; Amel Brahim-Mathiron (Open Heart)
Introduction The impact of sex on coronary artery disease prognosis is debated. It has been postulated that women receive less prompt treatment compared with men, potentially adversely affecting their prognosis by significantly increasing the risk of morbidity and mortality. We aim to investigate the influence of sex on the timing and clinical outcomes of ST-segment elevation myocardial infarction (STEMI) patients using a controlled Swiss registry.Methods and results Based on the Fribourg STEMI Fast Track Registry, 1177 patients (288 women, 889 men) with >12 months clinical follow-up were selected. Women had longer first medical contact to reperfusion times (1.31 (1.14–2.00) vs 1.27 (1.09–1.54) hours, p=0.035) but similar total ischaemic times (3.04 (2.15–4.50) vs 2.56 (2.07–4.38) hours, p=0.064). Men had higher rates of diabetes, smoking and dyslipidaemia, while women had higher hypertension and renal insufficiency rates. No significant sex differences in clinical outcomes were observed at 1-year and 5-year follow-ups.Discussion The study found sex differences in patient profiles and minor treatment delays for women, which did not significantly affect outcomes. Efforts to improve sex equity in STEMI care are effective, as no significant outcome differences were observed. Disparities are more related to patient characteristics than sex.Conclusion Despite slight delays and different risk profiles for women with STEMI, clinical outcomes are similar between sexes. Ongoing efforts are needed to ensure sex equity in acute coronary syndrome management.Trial registration number NCT04185285.